Promosi Kesehatan Dengan Menggunakan Media Aplikasi Canva Di RS Mitra Sejati - Aulia Dini; Dela Salma; Gembira Pasaribu; Erinda Pasaribu (STIKES Columbia Asia Medan, 2025)
Health promotion is an important effort to improve people’s knowledge, attitudes, and behaviors toward health. The use of attractive, creative, and easy-to-understand media is one of the key factors for the success of health promotion. This study/activity aims to determine the effectiveness of using the Canva application as a health promotion medium at Mitra Sejati Hospital. The method used was the development of health promotion materials in the form of posters, leaflets, and digital presentations with communicative visual designs, which were then disseminated to patients and hospital visitors. The results showed that health promotion media designed using Canva were able to attract the audience’s attention, increase their understanding of the health topics delivered, and motivate healthy behaviors. In conclusion, the use of the Canva application can serve as an effective and innovative health promotion medium that aligns with technological developments in the digital era.